Baseline neuronal antibodies in patients with small cell lung cancer are not necessarily associated with post-immune checkpoint inhibitors neurotoxicities - Rossi, Simone; Andrini, Elisa; Rinaldi, Rita; Silvestri, Tania; Formelli, Maria Giovanna; Di Odoardo, Adriana; Lenzi, Barbara; Guarino, Maria; Campana, Davide; Lamberti, Giuseppe (Frontiers in Immunology, 2025)
Background and objectivesAutoantibodies against intracellular neuronal antigens (IC-Abs) can be found in neurologically asymptomatic patients with small cell lung cancer (SCLC) and have been proposed as a predictive biomarker for the development of post-immune checkpoint inhibitors (ICIs) neurotoxicities. The aim of this study was to prospectively evaluate the association of baseline neural antibodies with immune-related adverse events (irAEs) - including neurological irAEs (n-irAEs) - and oncological outcomes in patients with SCLC following ICI therapy.MethodsIn this prospective cohort study, consecutive patients with SCLC eligible for treatment with ICI were assessed for the presence of IC-Abs with both indirect immunofluorescence (IIF) tissue-based assay (TBA) and line-blot and underwent baseline neurological evaluation prior to ICI initiation. Patients were longitudinally monitored for irAEs occurrence and oncological outcomes. Comparisons between groups, time-to-event and multivariable analyses were performed.ResultsFifty-six neurologically asymptomatic patients with SCLC (median age 70.5 years, 38% female) were included. Nineteen (34%) had IC-Abs prior to ICI-treatment (anti-Hu, n=7 [37%]; anti-Zic4, n=6 [32%]; anti-SOX1, n=3 [16%]; anti-SOX1 and anti-Zic4, n=2 [11%]; anti-Purkinje cerebellar cells, n=1 [5%]). Following ICI-treatment, two patients (3.6%) developed a n-irAE (one with baseline anti-Hu antibodies; one without baseline IC-Abs). The presence of baseline IC-Abs was not associated with an increased incidence of n-irAEs. However, anti-Hu antibody positivity was associated with an increased risk of irAEs of any type (OR 8.3; 95% CI, 1.22–56.54). A non-significant trend toward longer progression-free survival was observed in anti-Hu–positive patients (9.4 vs 5.7 months; p=0.10).DiscussionThe presence of baseline IC-Abs may not be associated with the occurrence of post-ICI neurotoxicities in patients with SCLC. However, anti-Hu antibody positivity correlates with an increased risk of irAEs of any type. Larger studies are needed to assess the safety of ICI therapy in patients with SCLC harbouring neural antibodies and to investigate their potential role as predictive biomarkers of post-ICI neurotoxicities.